課程變革的趨勢和具澳門特色的課程發展 - Ge, Rochelle Yun (Curriculum and Teaching in a Global Perspective: Reforms, Opportunities and Challenges Symposium, 2023)

澳門特殊與融合教育的發展及教師培訓 - Ge, Rochelle Yun (知行合一特殊教育高質量發展國際研討會, 2023)

Understanding Chinese Model of Government-University-Industry Collaborations in Research and Education: The Case of Macau SAR. - Ge, Yun (IFCU’s International Centre for Research and Decision Support’s Research Talk series, 2023)
Higher Education in Macau has been benefiting from a multi-layered institutional environment under China’s One-Country-Two-Systems. This presentation introduces research and education policies and practices of Macau universities under China’s national plan of the Greater Bay Area development. It aims to demonstrate and analyze how higher education actors collaborate with local and regional governments and industrial sectors in human capital formation and research innovations.